Monetary policy under an exchange rate anchor - El Hamiani Khatat, Mariam,Buessing-Loercks, Mark,Fleuriet, Vincent (International Monetary Fund, 2020)
This paper argues that there is scope for monetary policy under an exchange rate anchor, and discusses the related monetary policy design and implementation. It shows that the exchange rate can be used as the main monetary policy instrument while the policy rate can target the exchange rate. An exchange rate anchor is compatible with an inflation objective, provided fiscal dominance is not an issue, monetary conditions are supportive of the peg, and the level of international reserves is adequate. The paper argues that, while an exchange rate anchor is more prone to policy inconsistencies, there is ample scope for strengthening monetary policy design and implementation under soft pegs. In that context, the principles of dichotomy and interest rate parity are critical
10.5089/9781513556383.001
Keywords: Graue Literatur; Banks and Banking; Money and Monetary Policy; Policy Objectives; Policy Designs and Consistency; Policy Coordination; Foreign Exchange; Current Account Adjustment; Short-term Capital Movements; Monetary Policy; Interest Rates: Determination; Term Structure; and Effects; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Development Planning and Policy: Trade Policy; Factor Movement; Foreign Exchange Policy; Currency; Foreign exchange; Monetary economics; Exchange rates; Exchange rate arrangements; Exchange rate anchor; Central bank policy rate; Banking; Financial services; Exchange rate policy; Foreign exchange; Monetary policy; Interest rates; Banks and banking; monetary policy framework; exchange rate regime; interest rate parity; monetary policy rules; monetary operations; foreign exchange interventions